SPACE BOOK - UNIVERSITY SPACE MANAGEMENT (CIPEEX, 2024)
THIS PROJECT AIMS TO CREATE AN INNOVATIVE PLATFORM TO SIMPLIFY THE SCHEDULING OF UNIVERSITY SPACES IN A CONSTANTLY EVOLVING ACADEMIC LANDSCAPE. BASED ON AGILE METHODOLOGIES, THE TEAM WILL ANALYZE THE NEEDS OF THE ACADEMIC COMMUNITY, DESIGN AN EFFICIENT USER INTERFACE AND DEVELOP A SECURE AND EFFECTIVE SYSTEM. THE AIM IS TO FACILITATE FAST AND EFFICIENT BOOKINGS, REDUCE SCHEDULING CONFLICTS AND IMPROVE THE MANAGEMENT OF UNIVERSITY RESOURCES, CONTRIBUTING TO ACADEMIC SUCCESS AND THE MODERNIZATION OF ACADEMIC MANAGEMENT.
Keywords: Platform; Scheduling; University